Circumferential pure shear test of thin-walled aluminum alloy tubes. Issue 1 (1st December 2022) - Zhang, S N; Wang, X S; Lin, Z Y; Liu, G
Abstract : In order to obtain the pure shear deformation characteristics along the circumferential direction of tubes, a circumferential shear test for thin-walled tubes is proposed in this paper. The experimental device consists of a tubular sample and two cylindrical mandrels with shear plates. The torque along the circumferential direction was applied to the tubular sample by the two shear plates to make the pre-set shearing zone of the sample under a circumferential pure shear stress state. The two cylindrical mandrels support the inner wall of the tube to avoid buckling so that the pure shear stress state can be maintained during the whole deformation process. A 5052 aluminum alloy tube with an outer diameter of 50 mm and a wall thickness of 1.2 mm was used in the test. It is shown through simulation and experiment that shear deformation is concentrated in the pre-set shearing zone. This test can be used to obtain the circumferential pure shear stress-strain relationship.